Characterization of Fe-Chitosan-Succinate- NN’-Methylene Bis-Acrylamide as Ion Imprinted Polymer - M. Suhartini; S. Anwar; A. Saefumillah; S. Prayitno; S Sudirman (PPIKSN-BATAN, 2020)
High level of phosphate in the aquatic environment can reduce the amount of dissolved oxygen in the water which is harmful to the preservation of aquatic ecosystems. However, ion-imprinted polymer (IIP) is available to adsorp tripolyphosphate (TPP). In this study, Fe (III)-chitosan-succinate-tripolyphosphate complex was synthesized with NN’-Methylene Bis-Acrylamide (MBA) as a crosslinking agent and gamma-ray as reaction initiator. The aim of the study is to observe the physical and chemical characteristics of radiation-induced crosslinking of IIP in the present of MBA. The results show that tripolyphosphate ion adsorption capacity on the Fe-chitosan-succinate-MBA ion-imprinted polymer improved by 75.62 % than that of the non-imprinted polymer.The Differential Scanning Calorimetry (DSC) analysis shows a significant difference in the endothermic, exothermic and glass transitions of chitosan, chitosan-succinate when compared to their complex salts. The Fourier Transform Infra-Red (FTIR) analysis shows the presence of tripolyphosphate groups bonded by Fe-Chitosan-succinate-MBA ion imprinted polymer. Scanning Electron Microscope (SEM) analysis of IIP exhibits a significantly difference surface shapes between IIP with template still within the polymer matrix and after removal.